OrpheusDB: A Lightweight Approach to Relational Dataset Versioning - Xu, Liqi; Huang, Silu; Hui, Sili; Elmore, Aaron J.; Parameswaran, Aditya (Proceedings of the ACM SIGMOD International Conference on Management of Data (SIGMOD DEMO), 2017)
We demonstrate ORPHEUSDB, a lightweight approach to versioning of relational datasets. ORPHEUSDB is built as a thin layer on top of standard relational databases, and therefore inherits much of their benefits while also compactly storing, tracking, and recreating dataset versions on demand. ORPHEUSDB also supports a range of querying modalities spanning both SQL and git-style version commands. Conference attendees will be able to interact with ORPHEUSDB via an interactive version browser interface. The demo will highlight underlying design decisions of ORPHEUSDB, and provide an understanding of how ORPHEUSDB translates versioning commands into commands understood by a database system that is unaware of the presence of versions. ORPHEUSDB has been developed as open-source software; code is available at http://orpheus-db.github.io.